Géoarchéologie des paysages littoraux le long du golfe sud‑eubéen (île d’Eubée, Grèce)au cours de l’Holocène (Geoarchaeology of coastal landscapes along the south Euboean gulf (Euboea Island, Greece) during the Holocene) - Ghilardi, M; Vacchi, M; Currás, A; Müller Celka, S; Theurillat, T; Lemos, I; Pavlopoulos, K (Association française pour l’étude du quaternaire, 2018)
A joint geoarchaeological research programme developed by CNRS, together with the Swiss School of Archaeology in Greece, the British School at Athens, the Harokopiou University of Athens and the local archaeological services (Ephorate of Antiquities of Euboea), has endeavored to reconstruct the Holocene coastal landscape evolution in the vicinity of major archaeological sites along the southwest shoreline of Euboea Island (Greece), together with the history of human occupation. The sites of Lefkandi, Eretria, Amarynthos and the Lilas delta were selected for their rich archaeological record. During the work, 26 boreholes were drilled in the corresponding coastal plains. Laboratory analysis comprised the identification of mollusks and ostracods, together with granulometric analyses of the sediments, to characterize the different sedimentary environments. 71 radiocarbon dates provided a robust chronostratigraphic framework for the studied sites. In addition, a pollen sequence from Amarynthos was studied to reconstruct the vegetation history from ca. 5.500-4.300 (Neolithic times) and from 1.100-850 cal. BC (Early Iron Age). The results enable us to: (i) Reconstruct the Holocene shoreline migrations from the Lilas delta, in the north, to Amarynthos in the south. Three major phases of shoreline progradation are recorded at the end of the IVth/beginning of the IIIrd Millennium BC, at the beginning of the Ist Millennium BC and during the Ottoman period (xvth-xixth Cent. AD), while a marine incursion occurred only in Eretria during the IInd millennium BC; ii) reconstruct the sea level curve for the last 8 millennia in the West-Central Aegean Sea. A significant role of local tectonic vertical movements (uplift) is evident, attested by the presence of several hiatuses in sedimentation; (iii) reconstruct for the first time the vegetation history in the surroundings of Amarynthos, from Neolithic times and Early Iron Age, within the broader South Aegean-Attica environmental context, which has never been achieved before. Human activities (grazing and cereal cultivation) are recorded since at least Late Neolithic times where an open landscape dominated until at least the Early Iron Age.